Spontaneous Conduplicatio Corpore in Chorioamnionitis Case a case report - Hamka Koerslo; Eddy R Pangaribuan (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Chorioamnionitis is an acute infection of the amnion and chorion membranes with significant maternal and fetal morbidity. This case report describes a rare presentation of spontaneous conduplicatio corpore in a 22-year-old primigravida at 32–33 weeks of gestation with clinical chorioamnionitis following prolonged preterm premature rupture of membranes. The patient presented with fever, foul-smelling amniotic fluid, and absent fetal movement. Spontaneous delivery occurred with an atypical fetal posture, demonstrating conduplicatio corpore. This report highlights the importance of adequate antenatal care, prompt recognition of infection, and management of high-risk pregnancies to prevent adverse outcomes.